Simulating Ocean Surface Condition on an Extreme Weather Using Hydrodynamic 3D Model - Mahagnyana, Mahagnyana; Sujiono, Eko Hadi; Palloan, Pariabti; Rahma, Nayla Alvina (Institut Teknologi Sepuluh Nopember, 2024)
Research regarding sea surface condition during the coastal flood in Parepare 6 December 2021 has been carried out. In this research, the Delft3D model will be utilized to simulate the significant wave height (Hs) and direction, tide (η), and total water level (TWL) using input data from ECMWF ERA-5, including zonal (u) and meridional (v) wind, as well as surface air pressure data (p). The model’s output demonstrate that the model is capable of accurately simulating the Hs and η, utilizing 2x2 gridded satellite data and the tide observation station of BIG, respectively. Hence, we conducted simulations to explore the interaction between Hs and η in the form of TWL in Parepare Bay, focusing in Bacukiki Barat and Ujung Districts on Desember 6, 2021. The results indicate that the maximum TWL for these two districts was 2.3376 meters dan 2.2096 meters, consecutively, both of which propagated towards the Parepare Coast. These extreme TWL height were exacerbated by the extreme rainfall occurring in Parepare City within 4-7 December 2021, which is exceeding 200 mm/day. The ECMWF ERA-5 model also revealed that the presence of strong winds blowing from The Java Sea to The Makassar Strait at speeds of around 25-30 knots, which is suspected to be the underlying cause of the high waves observed over the Makassar Strait.